A benchtop closed-loop system controlled by a bio-inspired silicon implementation of the pancreatic beta cell. - Oliver,N; Georgiou,P; Johnston,D; Toumazou,C (J Diabetes Sci Technol, 2009)
UNLABELLED: The normal pancreatic beta-cell membrane depolarizes in response to increasing concentrations of glucose in a bursting pattern. At <7 mM (126 mg/dl), the cell is electrically silent. The bursting pulse width increases as glucose rises >7 mM (126 mg/dl) until a continuous train of bursting is seen at >25 mM (450 mg/dl). A bio-inspired silicon device has been developed using analogue electronics to implement membrane depolarization of the beta cell. The device is ultralow powered, miniaturized (5 x 5 mm), and produces a bursting output identical to that characterized in electrophysiological studies. OBJECTIVE: The goal of this study was to demonstrate the ability of silicon implementation of beta-cell electrophysiology to respond to a simulated glucose input and to drive an infusion pump in vitro. METHOD: The silicon device response to a current source was recorded at varying simulated glucose concentrations. Subsequently, the bursting response to a changing analyte concentration measured by an amperometric enzyme electrode was converted to a voltage, driving a syringe pump loaded with a 50-ml syringe containing water. RESULTS: Bursting responses are comparable to those recorded in electrophysiology. Silicon beta-cell implementation bursts with a pulse width proportional to concentration and is able to drive an infusion pump. CONCLUSION: This is the first in vitro demonstration of closed loop insulin delivery utilizing miniaturized silicon implementation of beta-cell physiology in analogue electronics.